The effectiveness of implementing European Union structural funds in the 2014-2020 programming period: A comparative analysis of Poland and Italy - Krzysztof Lewandowski (Comparative Economic Research. Central and Eastern Europe, 2023)
The aim of the European Union's cohesion policy is to reduce development inequalities between the regions of the Member States and to increase economic, social, and territorial cohesion. Expenditures on it account for one-third of the European Union (EU) budget. Therefore, the appropriate and effective use of the structural funds plays a very important role. The purpose of the paper is to show the effectiveness of using the EU's structural funds in two of the largest beneficiary countries in the programming period 2014-2020. The first part of the paper presents the efficiency and effectiveness of using EU structural funds and the barriers related to their implementation, as well as the main characteristics of the 2014-2020 programming period. The second part contains a statistical analysis of the effectiveness of implementing the cohesion policy in Poland and Italy, comparing the amounts of planned and spent funds in the analyzed period. The main method is the statistical analysis, which includes asummary of the amount of allocated funds and their use, as well as a calculation of the percentage of structural funds used. The theoretical part shows potential problems related to the implementation, while the statistical part shows the scale of the problem and the areas with the greatest problems with implementation in both countries.The analysis takes into account thematic objectives, as well as national and regional operational programs.
Keywords: F15; F36; R11; 330; effectiveness; European Union; cohesion policy; structural funds; effectiveness